Impacts of basin restriction on geochemistry and extinction patterns: A case from the Guadalupian Delaware Basin, USA - Smith, Benjamin P.; Larson, Toti; Martindale, Rowan C.; Kerans, Charles (Earth and planetary science letters, 2020)
Geochemical data from carbonates often constrain the nature of environmental change during biotic turnover events. Many ancient carbonates, however, formed in geographically-isolated basins subject to local environmental factors, resulting in varying extinction rates between open ocean and restricted settings. It follows that high-resolution data from restricted basins may help unravel poorly-understood biotic crises such as the Mid-Capitanian extinction, which had especially high extinction rates in restricted settings. This study examines factors controlling salinity, stratification, and oxygenation in the Capitanian (Middle Permian) Delaware Basin, USA. Elemental and carbon isotope measurements from time-equivalent strata reveal differences between shallow- and deep-water masses, pointing to local controls such as stratification and de-oxygenated bottom water. Basinal dolomites and evaporites mark periods of elevated salinity tied to sea-level lowstands, which correspond with turnovers in fusulinid and brachiopod communities. Faunal turnover in the Delaware Basin demonstrates a fundamental attribute of restricted basins: water chemistry is often tightly coupled to physical process such as sea level change. We suggest that the relationships among sea level fluctuations, chemical changes, and biotic turnover may explain why the Capitanian mass extinction was more severe in isolated basins than the open ocean. •Sea level fluctuations and basin closure triggered changes in salinity and oxygenation.•Local changes drove decoupling of basinal δ13C records from global seawater.•Changes in basin water chemistry correlate with faunal and ecological turnover.•Local effects likely contributed to high Capitanian extinction rates in isolated basins.